Alleviating concrete placement issues due to congestion of reinforcement in post-tensioned haunch-slab bridges - Sheedy, Patrick (Kansas State University, 2011)
A flowable hybrid concrete mix with a spread of 17 to 20 inches was created with a superplasticizer to be used in post-tension haunch-slab (PTHS) bridges where rebar congestion is heaviest. The mix would allow for proper concrete consolidation. A conventional concrete mix with a slump of three to four inches was also created to be placed on top of the hybrid mix. The conventional mix would be used to create a sloping surface on the top of the concrete. The two mixes could be combined in the PTHS bridge deck and act as one monolithic specimen. Standard concrete tests such as compressive strength, tensile strength, modulus of elasticity, permeability, freeze/thaw resistance, and coefficient of thermal expansion were determined for the mixes and compared. Core blocks were cast using both mixes and composite cores were drilled. The cores were tested and their composite split-tensile strengths were compared to the split-tensile strengths of cylinders made from the respective mixes. A third concrete mix was made by increasing the superplasticizer dosage in the hybrid concrete mix to create a self-consolidating concrete (SCC) mix with a 24-inch spread. The SCC mix was created as a worst-case scenario and used in the determination of shear friction. Eighty-four push-off shear friction specimens were cast using the SCC mix. Joint conditions for the specimens included uncracked, pre-cracked, and cold-joints. Uncracked and pre-cracked specimens used both epoxy- and non-epoxy-coated shear stirrups. Cold-joint specimens used both the SCC mix and the conventional concrete mix. Joint-conditions of the cold-joint specimens included a one-hour cast time, a seven-day joint with a clean shear interface, and a seven-day joint with an oiled shear interface. The shear friction specimens were tested using a pure shear method and their results were compared to the current American Concrete Institute code equation.
Keywords: Concrete; Shear friction; Self-consolidating concrete; Cold-joint; Civil Engineering (0543)